The strategic role of HR management in increasing the company's excellence and competitiveness - Anjani, Linda; Fajri, Marwah Laelatul; Rohmatiati, Rohmatiati; Alwi, Muh. (Indonesian Journal of Multidisciplinary Science, 2024)
Human resources are the main asset for the company. Many companies have the view that HR is part of assets that cannot be replaced. But not infrequently companies do not know the strategic role of how to manage these valuable assets. Through this research, we want to explain that there is a strategic role in HR management in increasing the company's excellence and competitiveness. This research is a descriptive qualitative research approach, or included in the type of grounded theory study. A research method that uses a perspective by examining a theory. From the results of the discussion in this study, in building a superior and competitive company, an HR management paradigm is needed that looks at various aspects, namely socio-economic, environmental-economic, and social aspects of the company. Then in the strategic HR management paradigm, not all human resources can be said to be assets, meaning that there are characteristics that must be owned by human resources who are considered assets. Then from the character possessed, it is necessary to have an HR management strategy so that it can be optimally well in increasing the company's excellence and competitiveness. These include accommodating, integrative, interactive. Then, in creating superior and competitive HR management, four approaches are used, including. Strategic Partner, Administration Expert, Employee Champion, Change Agent.